Syzygy of Sexual Polarities: A Juginan Psychological Elucidation of Ode to Grecian Urn - Khan, Imdad Ullah; Ali , Akbar; Hakeem, Memoona (Linguistics and Literature Review, 2023)
This study examines the psychological symbolism in Keatsian poetry using analytical psychology. John Keats ‘Ode on a Grecian Urn’ is steeped in psychological, symbolic, and analytical perspectives, which are essential components of Jungian psychology/archetypal analysis. The current study aims to scrutinize the psychological and symbolic perspectives of Keats’s poem to understand the depth of psychic integration and archetypes in the text. This study analyzes ‘Ode on a Grecian Urn’ by deploying Carl Jung’s concepts of syzygy or complementation of psychic energies of anima in the males and animus in the females. The term syzygy signifies a union of opposites like anima and animus and the conscious or collective unconscious. This process of complementation or complementary opposite of integration in the ode has symbolic interaction between the conscious male persona (animus) and the collective unconscious female persona (anima). Based on a close reading of the poem from a Jungian perspective, the current study provides a psychological understanding of poetic creation by underlying the conscious acts and thinking of the author as psychic interactions. This study aims to understand the symbolic representation of opposing psychic energies in Keatsian poetry. Moreover, the study analyzes the interpretation and the balance of male and female energies in Keats’ poetry mean for the conscious and unconscious parts of the mind, and its effect on the poetic creativity and inner peace of the author. Thereby, the study elaborated that Keatsian poetry is a true depiction of Jungian psychology.